(untitled) (Agricultural Engineering, 2018)
The aim of this study was to determine the effect of ultrasound waves on mechanical properties of organic bread. Mixed grain bread baked at a local bakery according to its original recipe was the material subjected to testing. Prior to baking, the dough was sonicated at frequencies of 20 kHz and 40 kHz for 3 minutes, and at a frequency of 100 kHz for 3 minutes and 6 minutes. The mechanical properties of the bread (compression test, penetration test and TPA) were examined after 24 h, 48 h and 72 h following the baking process. The maximum work obtained in the compression test after 24 h following the baking ranged from 616 N to 668 N. On the next day following the baking, the maximum work value ranged from 750 N to 898 N, while after 72 hours, it ranged from 988 N to 1135 N. In the penetration test, the following results were obtained: after 24 hours, the force value ranged from 2.71 N to 3.17 N; after 48 hours following the baking, it ranged from 4.90 N to 6.35 N; and after 72 hours following the baking, from 3.98 N to 6.88 N. As regards elasticity, the obtained results fell within the following ranges: after 24 hours following the baking, from 0.53 to 0.58; after 48 hours following the baking, from 0.43 to 0.55; and after 72 hours following the baking, from 0.40 to 0.45. Gumminess measured after 24 hours following the baking ranged from 8.75 N to 18.71 N; after 48 hours, from 10.83 N to 15.48 N; and after 72 hours, the gumminess values ranged from 15.57 N to 19.06 N. As regards chewiness, the following results were obtained: after 24 hours following the baking, from 8.00 N to 17.59 N; after 48 hours following the baking, from 9.77 N to 13.87 N; and after 72 hours following the baking, from 12.56 N to 16.85 N. The frequencies and durations of sonication applied changed no mechanical properties of the tested bread.